Substance use disorders: diagnosis and management for hospitalists. Issue 2 (3rd March 2020) - Pasha, Ahmed K.; Chowdhury, Arnab; Sadiq, Sanah; Fairbanks, Jeremiah; Sinha, Shirshendu
ABSTRACT: Substance use disorder is a significant health concern. Hospitalists manage patient with various forms of substance use disorder on a daily basis. In this review, we have tried to synthesize evidence together to give a brief, yet succinct, review of commonly encounters disorders; alcohol intoxication and withdrawal, opioid intoxication and withdrawal, cocaine intoxication and methamphetamine intoxication. We describe clinical features, diagnosis and management, which would serve as a great resource for hospitalist when managing these complicated patients.